The Effect and Safety of Iguratimod Combined With Methotrexate on Rheumatoid Arthritis: A Systematic Review and Meta-Analysis Based on a Randomized Controlled Trial - Zeng, Liuting; Yu, Ganpeng; Yang, Kailin; Hao, Wensa; Chen, Hua (Frontiers in Pharmacology, 2022)
Background: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease with inflammatory synovitis. Iguratimod (IGU) combined with methotrexate (MTX) therapy may have better efficacy and safety Methods: First, we searched randomized controlled trials (RCTs) of IGU+MTX in the treatment of RA through literature databases (such as Pubmed, Corkland Library, CNKI, etc.), and then conducted RCT quality assessment and data extraction. Finally, we used RevMan 5.3 for meta-analysis, STATA 15.0 for publication bias assessment, and GRADE tool for the evidence quality assessment of primary outcomes. This systematic review and meta-analysis was registered in PROSPERO (CRD42021220780). Results: This systematic review and meta-analysis included 31 RCTs involving 2776 patients. Compared with MTX alone, the ACR20, ACR50, and ACR70 of IGU+MTX are higher, while DAS28 is lower [ACR20: (RR 1.55, 95%CI 1.14 to 2.13, P=0.006); ACR50: (RR 2.04, 95%CI 1.57 to 2.65, P<0.00001); ACR70: (RR 2.19, 95%CI 1.44 to 3.34, P=0.00003); DAS28: (WMD -1.65, 95%CI -2.39 to -0.91, P<0.0001)]. Compared with MTX+Leflunomide, IGU+MTX has no significant difference in improving ACR20, ACR50, ACR70, but IGU+MTX improves DAS28 more significantly[ACR20: (RR 1.09, 95%CI 0.79 to 1.89, P=0.59); ACR50: (RR 1.07, 95%CI 0.64 to 1.78, P=0.81); ACR70: (RR 1.17, 95%CI 0.44 to 3.10, P=0.76); DAS28: (WMD -0.40, 95%CI -0.42 to -0.38, P<0.0001)]. Compared with MTX+Tripterygium subgroup and MTX only subgroup, the incidence of adverse events of IGU+MTX group is of no statistical significance [MTX only: (RR 0.99, 95%CI 0.87 to 1.13, P=0.90); MTX+ Tripterygium: (RR 0.73, 95%CI 0.29 to 1.85, P=0.50)]. However, compared with MTX+ Leflunomide, the incidence of adverse events in the IGU+MTX group was lower (RR 0.74, 95%CI 0.62 to 0.88, P=0.0009). The quality of ACR70 was high; the quality of adverse events and ACR50 test was moderate. Conclusion: Compared with conventional therapy, IGU+MTX may be a safer and more effective therapy for RA patients. When the intervention method is [IGU 25mg Bid, MTX 10mg-25mg once a week], and the intervention lasts for at least 12 weeks, the curative effect may be achieved without obvious adverse events.